2018
DOI: 10.1038/s41598-018-33132-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Coal Mining on the Spatial Distribution of Potentially Toxic Metals in Farmland Tillage Soil

Abstract: Coal mining areas are prone to hazardous element contamination because of mining activities and the resulting wastes, mainly including Cr, Ni, Cu, Zn, Cd and Pb. This study collected 103 samples of farmland tillage soil surrounding a coal mine in southwestern Shandong province and monitored the heavy metal concentrations of each sample by inductively coupled plasma mass spectrometer (ICP-MS). Statistics, geostatistics, and geographical information systems (GIS) were used to determine the spatial pattern of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…The results show that the heavy metal elements in the surface soil within the research area are affected by human activities, and Hg is the most important pollution factor. This is consistent with the research result obtained by Li et al 45 .…”
Section: Resultssupporting
confidence: 94%
“…The results show that the heavy metal elements in the surface soil within the research area are affected by human activities, and Hg is the most important pollution factor. This is consistent with the research result obtained by Li et al 45 .…”
Section: Resultssupporting
confidence: 94%
“…Our findings expect to offer a theoretical support for Cr(VI) transformation of Cr(VI) to Cr(III) which has lower toxicity and less environmental mobility in soils. The methods used in the study might guide Cr(VI) restoration of soils in the reported coal mining areas where up to 500 mg Cr/kg soil in both coal mining soils and agricultural soils [ 48 , 49 ] and the 18–35 g TOC/kg soil in coal mining soils [ 50 ] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of these samples were tested for arsenic, beryllium, cadmium, nickel, lead, antimony, selenium and vanadium. These heavy metals are common by-products of coal mining and coal mining waste (Lemly 2009;Li et al 2018;National Research Council 2008) and the samples were tested to determine the effect of coal mining and coal mining waste on Mill Creek Ravine and Ross Acreage. The ten samples were chosen from across both Area 1 and Area 2: five were from a series of discrete creek silt layers covering occupation layers in Area 2, while the other five were taken from levels with high concentrations of coal waste in Area 1.…”
Section: Archaeology Of Ross Acreagementioning
confidence: 99%